Using PRP and human amniotic fluid combination for osteogenesis in rabbit socket preservation - Amir Hossein Moradi; Ali Kamalinejad; Nasrin Jalilian; Shantia Kazemi; Mozafar Khazaei (Wolters Kluwer Medknow Publications, 2015)
Introduction: Platelet-rich plasma (PRP) is used as an adjunct treatment during periodontal grafting surgery because of its capability of enhancing healing process. Amniotic fluid is a rich source of growth factors and hyaluronic acid (HA) and a good point to study its properties of wound healing and bone formation. The aim of this study was to evaluate the osteogenic properties of a combination of amniotic fluid and PRP in rabbit's dental socket preservation. Materials and Methods: The study population consisted of 24 healthy male laboratory rabbits (average weight 3,125 ± 185 gr) that were randomly allocated into four groups. PRP for the first group, human amniotic fluid (HAF) for the second group, a combination of PRP and HAF (PRHA) for the third group was used. In the fourth (control) group, no biomaterial was used. In each group, half of the rabbits were sacrificed at 4 weeks following surgery and the rest were sacrificed after 8 weeks. Histological analysis of biopsies of the sockets was performed using hematoxylin and eosin (H&E) staining. Data were analyzed using Statistical Package for the Social Sciences (SPSS) software (version 16) and P-value <0.05 was considered significance. Results: All three experimental groups showed positive effect on bone formation in terms of area of trabecular bone and number of osteocytes and also vessel formation. Socket preservation using HAF and PRHA showed the highest impact on bone formation. Socket preservation using HAF also had the highest impact on vessel formation. Conclusion: PRHA and HAF appear to be useful for enhancing bone formation. Since there was no difference between HAF and PRHA, it seems beneficial to use HAF due to its simplicity of application.